Quem poliniza Cereus jamacaru? - Zanina, Dalva Neta e (2013)
The Cereus jamacaru DC cactus is an important species for the Brazilian Northeast. Has developed many studies and uses of the plant, but has not been established which pollinator in areas of natural distribution. The aim was to identify the most effective pollinator for form and function C. jamacaru flower. Data collection was done in a fragment of Caatinga where we collected data on phenology, morphology and floral biology beyond search visitors. Fruits were numbered 695young flowers, 175 flowers and 21 fruits. The cactus flowering displays multiple bang type. The flowers are hermaphrodite. The hypanthium is tapered 6.5 cm length, 3 cm in diameter and 0.6 cm opening in the base. The nectariferous chamber is formed by the base of the stamens and has the opening with some kind of lock by the stylus. According to the morphological evidence comparing pollination by bats and moths observed most of the arguments in favor of chiropterophily. We simulate visits per Glossophaga soricina and got perfect compatibility, however we did not observe any animals visit with optimal fit. The visitor who came closest pollinator behavior was Xylocopa sp, a large bee. Probably this bee was responsible for the formation of the few fruits.